ATP-binding cassette transporter expression is widely dysregulated in frontotemporal dementia with TDP-43 inclusions - Katzeff, Jared S.; Lok, Hiu Chuen; Bhatia, Surabhi; Fu, YuHong; Halliday, Glenda M.; Kim, Woojin Scott (Frontiers in Molecular Neuroscience, 2022)
The human brain is highly enriched in lipids and increasing evidence indicates that dysregulation of lipids in the brain is associated with neurodegeneration. ATP-binding cassette subfamily A (ABCA) transporters control the movement of lipids across cellular membranes and are implicated in a number of neurodegenerative diseases. However, very little is known about the role of ABCA transporters in frontotemporal lobar degeneration with TDP-43 inclusions (FTLD-TDP), which is a common form of younger-onset dementia. We therefore undertook a comprehensive analysis of the expression of ABCA transporters (ABCA1–13) in five key brain regions (amygdala, inferior temporal cortex, superior frontal cortex, cerebellum and parietal cortex) in FTLD-TDP and controls. We found that the expression of ABCA2, ABCA3, ABCA4, ABCA7, ABCA9, ABCA10 and ABCA13 was significantly altered in FTLD-TDP in a region-specific manner. In addition, the expression of ABCA transporters correlated specifically to different neural markers and TARDBP. These results suggest substantial dysregulation of ABCA transporters and lipid metabolism in FTLD-TDP and these changes are associated with neuroinflammation.